2015
DOI: 10.1166/jnn.2015.10410
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tricyclopentadiene Over Nanoporous MCM-41 Catalysts

Abstract: The objective of this study is to evaluate the catalytic potential of metal oxide/MCM-41 catalysts in dicyclopentadiene oligomerization/dicyclopentadiene oligomer isomerization. Molybdenum oxide, tungsten oxide, and titanium oxide were loaded on MCM-41 using the modified atomic layer deposition method. The amount of the acid site with weak strength has been increased through metal oxide deposition. The oligomer yield in dicyclopentadiene oligomerization/dicyclopentadiene oligomer isomerization did not change w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Acid sites are generated with the introduction of GaN through ALD. In the TPD curves of all ALD GaN/MCM‐41 catalysts peaks at around 200 °C and 380 °C are observed, which respectively correspond to weak and medium strength acid sites [54,55] . Moreover, for sample 500‐3c‐GaN/MCM‐41 an extra desorption peak at around 450 °C is observed, which suggests the existence of medium to strong acid sites [56] .…”
Section: Resultsmentioning
confidence: 99%
“…Acid sites are generated with the introduction of GaN through ALD. In the TPD curves of all ALD GaN/MCM‐41 catalysts peaks at around 200 °C and 380 °C are observed, which respectively correspond to weak and medium strength acid sites [54,55] . Moreover, for sample 500‐3c‐GaN/MCM‐41 an extra desorption peak at around 450 °C is observed, which suggests the existence of medium to strong acid sites [56] .…”
Section: Resultsmentioning
confidence: 99%
“…The mesoporosity of Al-MCM-41(F) and higher Brønsted acid sites lead to a maximum conversion (52%) and selectivity (69%) at 150 °C. 14 Park et al 52 also used the MCM-41 catalyst and impregnated metal oxides such as molybdenum, tungsten, and titanium oxides to convert endo-DCPD. The oligomerization and isomerization reactions occurred at 150 °C.…”
Section: Other High Energy Density Fuelsmentioning
confidence: 99%
“…Park et al studied the performance of the MMZ H-beta catalyst in a fixed bed reactor (FBR) at 165 °C and 1.01 MPa for the oligomerization of endo-DCPD. They compared this with their earlier work, 52 which was performed in a batch reactor (BR) (150 °C, 4.2 wt % catalysts, and 150 rpm). It was observed that the total oligomers yield was 28.5%, which was close to 29.3% performed in the batch reactor after a 3 h run.…”
Section: Other High Energy Density Fuelsmentioning
confidence: 99%
“…We call this reaction 'one-pot DCPD oligomerization and TCPD isomerization'. In previous studies, it was reported that some kinds of mesoporous materials [6,10,11], microporous zeolites [6,9], and ionic liquids [12] are useful for DCPD oligomerization or TCPD isomerization in a batch reactor. On the other hand, the results of thermal oligomerization of DCPD at 2 h time-on-stream in a continuous reactor have been reported by Zhang et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, a continuous-flow reaction over a heterogeneous catalyst was investigated for the first time in one-pot DCPD oligomerization and TCPD isomerization processes. The mesoporous material prepared from commercial zeolite beta (MMZ Hb ) was utilized as a catalyst [10]. In addition, this study focused on the catalytic performance of the regenerated catalyst in comparison with the fresh catalyst.…”
Section: Introductionmentioning
confidence: 99%